2020
DOI: 10.1111/1462-2920.15213
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus spp. eliminate Sclerotinia sclerotiorum by imbalancing the ambient oxalic acid concentration and parasitizing its sclerotia

Abstract: Sclerotinia sclerotiorum, a pathogen of more than 600 host plants, secretes oxalic acid to regulate the ambient acidity and provide conducive environment for pathogenicity and reproduction. Few Aspergillus spp. were previously proposed as potential biocontrol agents for S. sclerotiorum as they deteriorate sclerotia and prevent pathogen's overwintering and initial infections. We studied the nature of physical and biochemical interactions between Aspergillus and Sclerotinia. Aspergillus species inhibited sclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…It was found that oxalic acid accumulation led to lowering ambient pH and promoted Sclerotinia sclerotiorum sclerotial development 13 . Recently, it has also been reported that S. sclerotiorum sclerotial formation was inhibited by exogenous oxalic acid at 25 mM and higher 14 . In this study, oxalic acid also had a dual effect on the sclerotia formation of P. umbellatus : a low concentration of OA (ranging from 0.05 to 0.10 mg/mL) promoted sclerotia differentiation from mycelia, while a high concentration of OA (1.10 mg/mL and higher) inhibited the formation of sclerotia (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…It was found that oxalic acid accumulation led to lowering ambient pH and promoted Sclerotinia sclerotiorum sclerotial development 13 . Recently, it has also been reported that S. sclerotiorum sclerotial formation was inhibited by exogenous oxalic acid at 25 mM and higher 14 . In this study, oxalic acid also had a dual effect on the sclerotia formation of P. umbellatus : a low concentration of OA (ranging from 0.05 to 0.10 mg/mL) promoted sclerotia differentiation from mycelia, while a high concentration of OA (1.10 mg/mL and higher) inhibited the formation of sclerotia (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…showed efficient suppression against a broad range of plant pathogenic fungi, bacteria, and nematodes [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The suppressive effect of Aspergillus was explained by several mechanisms including direct mycoparasitism [ 31 , 32 ], indirect inhibitory secretome such as hydrolytic chitinase and β-glucanase enzymes [ 22 , 33 ], and organic acids [ 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…This work was established to evaluate the biocontrol potential for diverse species of Aspergillus on white mold disease of legumes caused by S. sclerotiorum under lab and greenhouse conditions. The examined species were genetically identified, and their organic acid profile was characterized in our previous work [ 37 ]. As a continuation, the morphological, microscopic, mycotoxigenic, and pathological attributes were characterized as well to demonstrate variability among tested species.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that oxalic acid accumulation led to lowering ambient pH and favored Sclerotinia sclerotiorum sclerotial development 13 . Recently, it has also been reported that S. sclerotiorum sclerotial formation was inhibited by exogenous oxalic acid of 25mM and higher 14 . Thus, oxalic acid played dual roles in sclerotial differentiation.…”
Section: Discussionmentioning
confidence: 92%